2019
DOI: 10.1002/anie.201910304
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(0)‐Catalyzed Directed syn‐1,2‐Carboboration and ‐Silylation: Alkene Scope, Applications in Dearomatization, and Stereocontrol by a Chiral Auxiliary

Abstract: We report the development of palladium(0)‐catalyzed syn‐selective 1,2‐carboboration and ‐silylation reactions of alkenes containing cleavable directing groups. With B2pin2 or PhMe2Si‐Bpin as nucleophiles and aryl/alkenyl triflates as electrophiles, a broad range of mono‐, di‐, tri‐ and tetrasubstituted alkenes are compatible in these transformations. We further describe a directed dearomative 1,2‐carboboration of electron‐rich heteroarenes by employing this approach. Through use of a removable chiral directing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(43 citation statements)
references
References 75 publications
1
41
0
1
Order By: Relevance
“…Mechanistic studies. In analogy to earlier work [34][35][36][37][38][39][40][41][42][43][44][45][46][47] , we surmised that the reaction may proceed by the general mechanism depicted in Fig. 2c, involving a sequence of alkene coordination, nucleopalladation, intramolecular oxidative addition, and reductive elimination.…”
Section: Scope Of Alkenessupporting
confidence: 66%
See 1 more Smart Citation
“…Mechanistic studies. In analogy to earlier work [34][35][36][37][38][39][40][41][42][43][44][45][46][47] , we surmised that the reaction may proceed by the general mechanism depicted in Fig. 2c, involving a sequence of alkene coordination, nucleopalladation, intramolecular oxidative addition, and reductive elimination.…”
Section: Scope Of Alkenessupporting
confidence: 66%
“…During the past 5 years, our laboratories have developed a variety of transition-metal-catalyzed, three-component directed alkene 1,2-difunctionalization reactions facilitated by the 8aminoquinoline (AQ) auxiliary, a strongly coordinating bidentate directing group. Using this strategy we and others have reported examples of hydrofunctionalization [21][22][23][24][25][26][27][28][29][30][31][32][33] , dicarbofunctionalization [34][35][36][37][38][39] , carboamination 40,41 , and carbo-/aminoboration [42][43][44][45] , among other transformations 46,47 (Fig. 1c).…”
mentioning
confidence: 94%
“…A palladium-catalysed highly regio-and stereoselective carbosilylation of b,g-unsaturated carbonyl compounds using Me 2 PhSi-Bpin (18) as the silicon pronucleophile and aryl/alkenyl triflates as electrophiles was presented by Engle and co-workers in 2019 (103a-f -104a-f, Scheme 32). 51 The reaction involves a highly regioselective Heck-type aryl-or alkenylpalladation followed by C-Si bond formation at the palladium-bearing carbon atom. A removable directing group (AQ) was installed to steer the incorporation of the silyl group to the proximal position through the formation of palladacycle intermediates.…”
Section: Scheme 25mentioning
confidence: 99%
“…In 2018, the first example of selective hydroarylation of 1,3‐diynes with arylboronic acids enabled by a dimeric Mn(I)‐catalyzed was reported by our laboratory . However, the major challenges for Mn‐catalyzed selective hydroarylation of alkenes stem from largely undeveloped elementary units, such as transmetallation and migratory insertion compared with Pd or Rh catalysts, which have already gained great momentum in transition metal‐catalyzed conjugate addition of organometallics to electron‐deficient alkenes (Scheme a) . The early stoichiometric experiments from Nicholson, Main and Woodgate showed that only five‐membered stable aryl manganacycles can be used successfully with highly reactive unsaturated esters or nitriles in the presence of trimethylamine N ‐oxide and Li 2 PdCl 4 (Scheme b).…”
Section: Methodsmentioning
confidence: 99%